The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Milk Production, Processing and Marketing 2019
DOI: 10.5772/intechopen.82592
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Properties of Camel Milk

Abstract: Camel is considered as one of the most important and ecologically harmless domesticated animals in the dry region of Asia and Africa. Camels have considerable economic importance not only as a draught animal, but also for their milk and its by-products. They can produce a significant amount of milk from poor feed as compared to any other dairy species. This characteristic, in addition to the growing recognition of the economic value, and health benefits of camel milk make it a center of attention for people, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…However, under refrigerated (7°C) condition, the shelf life of raw camel milk was similar to that of pasteurized camel milk, hence, the pasteurization had little effect on the ethanol stability of raw camel milk. It was found to be effective in case of cow milk only which corroborates our findings with those of earlier workers (Emletan and Mohammad 2003) Data presented in above table revealed that refrigeration caused significantly minimum lactic acid content owing to the reason that camel milk contains a greater content of antimicrobial components such as lysozymes, lactoferrin and immunoglobulins than do bovine milk (Konnuspayeva et al 2007, Benkerroum 2008, Yoganandi et al 2014, Kaskous 2016, Kumar et al 2016, Rahmeh et al 2019, Al Nohair 2021 in comparison to storage at 25°C, whereas CoB+ and alcohol content values were found significantly higher under refrigeration of both camel and cow raw as well as pasteurized milk samples.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…However, under refrigerated (7°C) condition, the shelf life of raw camel milk was similar to that of pasteurized camel milk, hence, the pasteurization had little effect on the ethanol stability of raw camel milk. It was found to be effective in case of cow milk only which corroborates our findings with those of earlier workers (Emletan and Mohammad 2003) Data presented in above table revealed that refrigeration caused significantly minimum lactic acid content owing to the reason that camel milk contains a greater content of antimicrobial components such as lysozymes, lactoferrin and immunoglobulins than do bovine milk (Konnuspayeva et al 2007, Benkerroum 2008, Yoganandi et al 2014, Kaskous 2016, Kumar et al 2016, Rahmeh et al 2019, Al Nohair 2021 in comparison to storage at 25°C, whereas CoB+ and alcohol content values were found significantly higher under refrigeration of both camel and cow raw as well as pasteurized milk samples.…”
supporting
confidence: 91%
“…Camel has proved as a potential milch animal which is such an obvious solution for improving human nutrition in the arid zones of the world, where hunger is endemic. Camel milk has an important role in human nutrition as it contains all the essential nutrients (El-Agamy et al 2009, Yoganandi et al 2014, Kaskous 2016, Kumar et al 2016, Rahmeh et al 2019, Al Nohair 2021 found in bovine milk. Fresh and fermented camel milk is used as a treatment for a series of diseases such as dropsy, jaundice, tuberculosis, asthma, etc.…”
mentioning
confidence: 99%
See 3 more Smart Citations